Revision of Zimbabwe's Agro-Ecological Zones - Desmond Manatsa; Terence Darlington Mushore; Isaiah Gwitira; Lucy Charity Sakala; Leo Hassan Ali; Abel Chemura; Gibbon Innocent Masukwedza; John Matimba Mupuro; Raymond Mugandani; Menas Wuta; Munyaradzi D Shekede; Nyaradzo Marilyn Muzira (2022)
Agriculture remains a key sector to the economy of Zimbabwe providing livelihoods to more than 70% of the population and supplying raw materials for the predominantly agro-based economy. Land degradation, climate change, loss of biodiversity and ecosystem services pose significant challenges for the majority of the people who derive their livelihoods from agriculture. Moreover, the agricultural sector is key to employment creation, raising living standards, alleviating rural poverty and assuring food and nutritional security. In this way, increased agricultural productivity through sustainable management of land and water resources offers an important opportunity for the country to achieve Sustainable Development Goals (SDGs). However, much of the agricultural sector is predominantly rain-fed and therefore highly sensitive to climate variability and change. The country is characterized by diverse climatic patterns with the eastern highlands receiving more than 1500 mm of rainfall while the southern and western parts of the country are dry and characterized by erratic rainfall of less than 500 mm per year. On the other hand, mean annual temperature decreases from about 23°C in the low-lying areas in the south western parts of the country to about 18°C in the eastern highlands. The diverse climatic pattern is a key determinant of vegetation pattern and soil characteristics. Since climate is the main determinant of agricultural practice, it is important to delineate geographical regions into homogenous zones where variations in climate determine the agricultural activities practised in these areas. To date, agricultural practice in Zimbabwe has been based on Agro-ecological Zones/Natural Regions, hereafter referred interchangeably as AEZs or simply Natural Regions (NRs), which were developed by Vincent and Thomas in the 1960s (Vincent and Thomas, 1960). These AEZs were later modified by the AGRITEX Department in 1984 and the revised map is hereafter referred to as AGRITEX (1984). Although the AEZs developed in the 1960s provided an adequate basis on which agricultural practice in the country was based, the changes induced by climate change has made the applicability of these zones difficult. Climate change has altered temperature and rainfall regimes thereby affecting patterns of agricultural practice relevant for different regions in the country. Current observations indicate that climate change has disrupted the normal climatic patterns in such a way that the traditionally recognized AEZs are no longer in tandem with the expected agricultural productivity, hence reduced agricultural yields. Despite the observed changes in the climatic pattern which directly affects crop and livestock production, agricultural practice in the country is still being planned based on the traditional AEZs developed in the 1960s with some slight modifications in 1984. This threatens the sustainability of the agricultural sector due to deployment of unsustainable agricultural practices which are incongruent with prevailing climatic conditions. This mismatch between land capability and agricultural practice leads to a number of undesirable outcomes such as land degradation, loss of biodiversity and ecosystem services and consequently results in poor performance of the sector, which is key to the economy of Zimbabwe. Poor agricultural yields reduce economic growth particularly for agro-based economies hence the need to restructure the agricultural sector to reflect current trends in climate. In response to the urgent need of aligning agricultural practice with the changing climatic patterns, the Government of Zimbabwe through the Ministry of Higher and Tertiary Education, Innovation, Science and Technology Development initiated a revision of the country’s agro-ecological zones. Based on the observed pattern of rainfall and temperature and their influence on agricultural practice, the revision of the AEZ had two main objectives: 1) to redefine the AEZs based on the vii current climate trend and recommend land-use practices for each zone, and 2) to develop an interactive software (Agro Zim mobile application) that would assist users of the updated AEZ to get important spatially explicit information required to guide agricultural practice in Zimbabwe. In this regard, geospatial technologies combined with rigorous statistical analysis of climatic data, field validation and stakeholder consultations were applied to redefine the AEZs of Zimbabwe. All geospatial layers important in determining agricultural practice together with rainfall and temperature were overlaid in a GIS environment in order to define homogeneous zones where different land-use practices were recommended. The main advantage of the current AEZ definition is that it goes beyond the conventional approach and includes an interactive Android based software that is not only user friendly but freely available. The Agro Zim App allows stakeholders to obtain information on the different farming activities in each AEZ. This application was developed after the realization that access to climate information and advisory services is key in enhancing agricultural productivity. The ease of information accessibility ensures that the marginalized and vulnerable small-scale farmers make more informed and timely decisions at the click of a button on their mobile phones. The redefined zones were validated through stakeholder consultation in all the provinces of Zimbabwe where user needs for the mobile application were also collected. The main finding of this study is that there are significant spatial shifts in AEZ between the original zones developed by Vincent and Thomas in 1960 and newly delineated zones. Specifically, a smaller proportion of the country are experiencing better climatic patterns than previously observed and were thus assigned to AEZ that are more productive than in the original classification. However, a larger proportion of the AEZ shifted towards drier and less productive categories. There was a general agreement based on climate data and stakeholder consultations that the region previously classified as NR V be split into NR Va and NR Vb to reflect the distinct climatic patterns that are now being experienced in this region. NR Vb was regarded as not suitable for sustaining any form of rain-fed agriculture, even the growing of drought tolerant crops. The results of this study underscore the importance of geospatial capabilities and Information Technology in optimising resource use in the agricultural sector. Most importantly, this report can serve as a valuable reference guide for policy makers, development practitioners, funding institutions, extension agents, farmers, researchers and other stakeholders who have interest in agriculture. Thus, the revised AEZ together with the mobile application present a new milestone for reviving the agricultural sector and restoring the country to its former bread basket status under a changing climate.